Comparison of bicarbonate‐buffered fluid and isotonic saline solution as Cell Saver washing fluids for packed red blood cells. Issue 11 (1st August 2013) - Huber, Dirk; Witt, Lars; Sümpelmann, Robert; Heinze, Larissa; Müller, Thomas; Lichtinghagen, Ralf; Osthaus, Wilhelm A.; Anderson, Brian
Summary Objectives Massive transfusion (MT) can cause severe electrolyte and acid–base disturbances in neonates and infants due to the unphysiological composition of packed red blood cells (PRBCs). Washing of the PRBCs using Cell Saver systems prior to MT is recommended for this reason. Aim The composition of normal saline (NaCl), the standard wash fluid for Cell Saver systems, is considerably different from that of physiological plasma. The aim of the study presented here was to investigate the effect of washing the PRBCs with a bicarbonate‐buffered hemofiltration solution (BB‐HS) in comparison with washing with NaCl and to evaluate the impact on electrolyte concentrations, acid–base balance and the stability of PRBCs. Methods In an experimental in vitro setting, PRBCs were washed with Cell Saver systems prepared with NaCl or BB‐HS as washing solutions. Before and after the washing procedure, electrolyte concentrations, acid–base parameters, adenosine triphosphate (ATP) and free hemoglobin (fHb) concentrations were measured. Results In both groups, the potassium concentrations decreased (baseline: 18.4 ± 5.17 mmol·l−1, end of study: NaCl 2.71 ± 1, 81 mmol·l−1, BB‐HS 2.50 ± 1.54 mmol·l−1, P < 0.05) while the acid–base balance improved only in the BB‐HS‐group (baseline: base excess −21.6 ± 3.52 mmol·l−1, end of study: NaCl −30.2 ± 1.42 mmol·l−1, BB‐HS −7.51 ± 2.49 mmol·l−1, P < 0.05). Furthermore, markers of erythrocyte stability such as fHb and ATP concentrations were improved in the BB‐HS‐group. Conclusions Washing of PRBCs with BB‐HS rather than NaCl results in a more physiological composition with improvements of electrolyte concentrations, acid–base balance and erythrocyte stability.